2009
DOI: 10.2176/nmc.49.379
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Hypoxia-Inducible Factor-1.ALPHA. and Vascular Endothelial Growth Factor in the Mechanism of Development of Chronic Subdural Hematoma

Abstract: Vascular endothelial growth factor (VEGF), a potent inducer of angiogenesis and vascular permeability in diverse physiological and pathological conditions, may be involved in the pathophysiology of chronic subdural hematoma (CSDH). The present study investigated the source and mechanisms for the induction of VEGF in CSDH by measuring the concentration of VEGF in the hematoma of 102 patients (122 hematomas) using the enzyme-linked immunosorbent assay technique. The relationship between the VEGF concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 18 publications
(26 reference statements)
2
55
0
2
Order By: Relevance
“…These authors concluded that VEGF may be involved in the pathogenesis of cSDH. Others have reported similar findings [6]. Higher levels of IL-6 in cSDH fluid and higher levels of VEGF and bFGF in the membranes have been reported in recurrent cSDHs when compared with nonrecurrent collections [7].…”
Section: Discussionsupporting
confidence: 54%
“…These authors concluded that VEGF may be involved in the pathogenesis of cSDH. Others have reported similar findings [6]. Higher levels of IL-6 in cSDH fluid and higher levels of VEGF and bFGF in the membranes have been reported in recurrent cSDHs when compared with nonrecurrent collections [7].…”
Section: Discussionsupporting
confidence: 54%
“…Imaging findings were highly suggestive for a giant cavernous malformation, after recent episode of hemorrhage. (10). The rate of bleeding is higher when the size of the lesion is greater than 10 mm and when the patient is aged 35 years or younger (11).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that the angiogenic response increases during hepatocarcinogenesis, and targeting VEGF significantly attenuated HCC development and metastasis (19). HIF-1α is also known as a target regulator of angiogenesis along with VEGF in various types of cancers (20,21). Since inhibition of VEGF could be due to inactivation of HIF-1α, VEGF/ HIF-1α may provide a potential target for a novel therapeutic strategy against HCC.…”
Section: Discussionmentioning
confidence: 99%